2007
DOI: 10.1111/j.1541-4329.2007.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Food Safety Knowledge Instrument

Abstract: Little is known about the food safety knowledge of young adults. In addition, few knowledge questionnaires and no comprehensive, criterion‐referenced measure that assesses the full range of food safety knowledge could be identified. Without appropriate, valid, and reliable measures and baseline data, it is difficult to develop and implement effective education efforts. Thus, the purpose of this study was to develop a comprehensive, valid, reliable food safety knowledge questionnaire. Questionnaire development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…The food safety section of the questionnaire was a selection of modified questions from a validated survey conducted by Byrd-Bredbenner et al (8) and a questionnaire used by Jay et al (13).…”
Section: Methodsmentioning
confidence: 99%
“…The food safety section of the questionnaire was a selection of modified questions from a validated survey conducted by Byrd-Bredbenner et al (8) and a questionnaire used by Jay et al (13).…”
Section: Methodsmentioning
confidence: 99%
“…These psychosocial measures were included because they are associated with a wide array of personal health choices and are thus key to understanding current food safety practices and creating interventions to change them (2-5, 13, 32, 44, 59). A detailed description of the developmental process used to create the psychosocial measures has been published previously (21,22). In brief, a pool of statements for each psychosocial measure was identified from the literature (11,18,20,28,31,33,35,40,41,44,48,53,56,69,71,73), created de novo, or both.…”
Section: Methodsmentioning
confidence: 99%
“…Food safety knowledge was measured using an online version of the Food Safety Knowledge questionnaire (Byrd-Bredbenner et al, 2007b). This is a validated and standardised questionnaire that covers many facets of safe food handling.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned, younger age groups are most at risk for inappropriate food handling behaviours and consequently foodborne disease. Byrd-Bredbenner et al (2007b) found that young adults aged 17 to 19 had the lowest food safety knowledge;…”
Section: Aimsmentioning
confidence: 99%